In-situ observations of volcanic ash clouds from the FAAM aircraft during the eruption of Eyjafjallajökull in 2010 - Johnson, Ben; Turnbull, Kate; Brown, Phil; Burgess, Rachel; Dorsey, James; Baran, Anthony J.; Webster, Helen; Haywood, Jim; Cotton, Richard; Ulanowski, Zbigniew; Hesse, Evelyn; Wolley, Alan; et al. (Journal of Geophysical Research: Atmospheres, 2012)
During April–May 2010 the UK Facility for Airborne Atmospheric Measurements (FAAM) BAe-146 aircraft flew 12 flights targeting volcanic ash clouds around the UK. The aircraft observed ash layers between altitudes of 2–8 km with peak mass concentrations typically between 200–2000 μg/m3, as estimated from a Cloud and Aerosol Spectrometer (CAS). A peak value of 2000–5000 μg/m3 was observed over Scotland on 14 May 2010, although with considerable uncertainty due to the possible contamination by ice. Aerosol size distributions within ash clouds showed a fine mode (0.1–0.6 μm) associated with sulphuric acid and/or sulphate, and a coarse mode (0.6–35 μm) associated with ash. The ash mass was dominated by particles in the size range 1–10 μm (volume-equivalent diameter), with a peak typically around 3–5 μm. Electron-microscope images and scattering patterns from the SID-2H (Small Ice Detector) probe showed the highly irregular shape of the ash particles. Ash clouds were also accompanied by elevated levels of SO2 (10–100 ppbv), strong aerosol scattering (50–500 × 10−6 m−1), and low Ångstrom exponents (−0.5 to 0.4) from the 3-wavelength nephelometer. Coarse-mode mass specific aerosol extinction coefficients (kext), based on the CAS size distribution varied from 0.45–1.06 m2/g. A representative value of 0.6 m2/g is suggested for distal ash clouds (∼1000 km downwind) from this eruption. Peer reviewed